Implementasi model pembelajaran STAD untuk meningkatkan motivasi dan prestasi belajar - Made Eka Adnyana (Lembaga Pengembangan Pembelajaran Penelitian dan Pengabdian Masyarakat Universitas PGRI Mahadewa Indonesia, 2020)
The low student learning outcomes are caused by the less optimal use of the learning model. Learning is still centered on the teacher, student motivation in learning is still lacking and teachers rarely reflect. So this classroom action research aims to increase motivation and learning achievement in biology through the application of the STAD learning model with the research subject class XI MIPA4 SMA Negeri 1 Kuta Selatan and the objects in this study are the motivation and achievement of learning biology. Student motivation data were collected through questionnaire sheets and learning outcome data were collected through learning achievement tests which were arranged in the form of objective tests. The data that has been collected are then analyzed descriptively. The results of this study indicate that there is an increase in student motivation and learning achievement after the application of the STAD learning model, this can be seen from the average student motivation in cycle I of 2.8 with sufficient criteria, while in cycle II the average value of student motivation is 3. , 7 with good criteria. The average student learning achievement in the first cycle was 61.17 with sufficient criteria, 61.17% absorption and 61.11% student learning completeness, while in the second cycle the average value of student learning achievement was 76.53 with good criteria, the absorption capacity of 76.53% and the completeness of student learning 94%. Rendahnya hasil belajar siswa disebabkan oleh kurang optimalnya penggunaan model pembelajaran. Pembelajaran masih terpusat pada guru, Motivasi siswa dalam pembelajaran masih kurang dan guru jarang melakukan refleksi. Penelitian tindakan kelas ini bertujuan untuk meningkatkan motivasi dan prestasi belajar biologi melalui penerapan model pembelajaran STAD dengan subjek penelitian adalah kelas XI MIPA4 SMA Negeri 1 Kuta Selatan dan objek dalam penelitian ini adalah motivasi dan prestasi belajar biologi. Data motivasi siswa dikumpulkan melalui lembar kuisioner dan data hasil belajar dikumpulkan melalui tes prestasi belajar yang disusun dalam bentuk tes objektif. Data yang telah terkumpul, kemudian dianalisis secara deskriptif. Hasil penelitian ini menunjukkan bahwa terjadi peningkatan motivasi dan prestasi belajar siswa setelah diterapkan model pembelajaran STAD, ini dapat dilihat dari rata-rata motivasi belajar siswa pada siklus I sebesar 2,8 dengan kriteria cukup sedangkan pada siklus II nilai rata-rata motivasi siswa adalah 3,7 dengan kriteria baik. Rata-rata prestasi belajar siswa pada siklus I adalah 61,17 dengan kriteria cukup, daya serap 61,17% dan ketuntasan belajar siswa 61,11 %, sedangkan pada siklus II nilai rata-rata prestasi belajar siswa adalah 76,53 dengan kriteria baik, daya serap 76,53 % dan ketuntasan belajar siswa 94%.